Tolerance to the herbicide clomazone and potential for changes of forest species (Bioscience Journal, 2017)
Clomazone has excelled among Brazilian non-target-site herbicides with high environmental impact. Its high solubility in water can result in leaching, contaminating groundwater and watercourses with possible riparian forest degradation. This situation can be mitigated by phytoremediation process. This study aimed to identify tree species tolerant to clomazone aiming to use them in bioremediation programs. Twelve forest species were evaluated: Inga marginata Willd, Handroanthus serratifolius (A.H. Gentry) S. Grose, Jacaranda puberula Chan, Cedrela fissilis Vell, Calophyllum brasiliense Cambess, Psidium myrsinoides Berg, Tibouchina granulosa Cogn, Caesalpinia ferrea Mart ex. Tul, Caesalpinia pluviosa DC, Terminalia argentea Mart & Zucc, Schinopsis brasiliensis Eng and Schizolobium parahyba (Vell). The statistical analysis was performed in a completely randomized block design with four replications. Three clomazone applications were made each 20 days (60, 80 and 100 days after planting); each application was equivalent to one-half of the recommended rate (2.0 L ha-1). The evaluated parameters were plant height, stem diameter, leaf number, leaf area and dry biomass. The forest species survived the clomazone application; and I. marginata, C. ferrea and S. brasiliensis showed increased tolerance to this herbicide, demonstrating potential for phytoremediation of areas contaminated by clomazone.